Vibrations of simply supported rectangular plates with varying thickness and same aspect ratio cutouts - Larrondo, Hilda Angela (2001)
Vibrations of simply supported rectangular plates with varying thickness and same aspect ratio cutouts were studied. Results obtained were compared with data available. Frequency coefficients were calculated using finite element method and were found to be in good agreement. No dynamic stiffening effect was noticed. Complete set of eigenfunctions can be used for rectangular plates of general anisotropy.